Multiple [33] Impacted teeth with Bilateral Maxillary dentigerous cyst in cleidocranial dysplasia: A Rare Syndromic Finding - Jigna S. Shah; Nidhi Susan Suresh; Freni K. Panchal (Indian Journal of Dental Sciences)
Cleidocranial dysplasia (CCD) is a rare autosomal disorder characterized by multiple impacted supernumerary teeth sometimes accompanied by follicular cysts. These patients may be first noticed by the dentist because of esthetic problems or delayed eruption of teeth. The aim of the study was to emphasize the importance of early diagnosis of CCD as multiple impacted teeth can give rise to dentigerous cyst in later stages. Two case reports describe the patients having typical features of CCD with impacted teeth and one of them was radiographically diagnosed with multiple dentigerous cysts. Early diagnosis of CCD and its management of impacted teeth with a multidisciplinary approach helps in avoiding the functional and pathological problems associated with it which include difficulty in mastication and poor patient self-esteem.